Hegemonic sanctions and global economic ramifications in the context of the Russian-Ukrainian conflict: A commentary - George Saridakis; Constantinos Alexiou; Roger Hoseinc; Nirvana Satnarine-Singhc (SPOUDAI - Journal of Economics and Business, 2022)
The outbreak of the Russian-Ukrainian military conflict has sent chills down the spines of policy makers around the world. In this paper we offer an account of the unfolding military intervention in Ukraine and its concomitant global economic ramifications. By assessing the events that have led up to an apparently inevitable showdown, through the lens of hegemonic order theory, we provide tentative, yet comprehensive, insights into Russia's military incursion. We further discuss the potential impact of the military conflict on international trade and the prices of energy, food, and metals. Whilst the analysis suggests that the efficacy of the economic sanctions will depend on a variety of factors, it is envisaged that the United States (US) is likely to be an important resource player that will, to a certain extent, side-line Russia's gas exports to Europe. Also, countries that primarily trade with Russia and which have refrained from imposing sanctions (e.g., Turkey and China) may benefit from increased trade with the rest of the world. In contrast, many energy- and food-dependent European economies are expected to face increased inflationary pressures in view of the depressed global economic environment and the ongoing supply-side disruption.
Keywords: E00; F18; F51; Q00; 330; conflict; Economic sanctions; energy market; food price; rare earth metals; Russia; theory of hegemony; trade; Ukraine